EVALUASI PENGENALAN TATA CARA BERWUDHU DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA GAMBAR PADA KELOMPOK B DI RA ASIAH KOTA PEKANBARU - Afiyah Afiyah; Melwani May Pratama; Rizky Nurhasanah; Ida Windi Wahyuni (UIR PRESS, 2019)
This study aims to introduce the procedure for ablution in the development of Islamic education through the medium of the slowdown in group B in RA Asiah, Pekanbaru city. The research was carried out because there were problems in the introduction of ablution procedures. The results of the observation on the evaluation of the introduction of ablution procedures in the development of Islamic education through the propagating media in group B in RA Asiah can be concluded that the introduction of the procedure for ablution through the image media is carried out optimally. The activity of introducing the procedures for the ablution of children given by educators goes according to the expectations and achievements of development, which are used as indicators of implementation on aspects of strength and balance